Cirugía transanal mínimamente invasiva: experiencia en un servicio especializado en Perú - López-Cutipa, Ever Frank (2024)
Introduction. Transanal minimally invasive surgery (TAMIS) is a procedure implemented in several centers around the world, showing high-quality local excision in rectal neoplasms. Objective. To describe the results of the experience of minimally invasive transanal surgery for local excision of rectal tumors at the Guillermo Almenara National Hospital, Lima, Peru. Methods. A descriptive, cross-sectional design study was carried out on all patients undergoing TAMIS during the period June 1, 2019 to December 31, 2023. Evaluating clinical, surgical, pathological variables and complications. Results. 16 patients were included. The mean age was 57 years (range 15 - 82). The mean size of the lesions was 3.5 cm (range 1.3 - 9 cm) and the mean height of the tumor at the anal margin was 8.6cm (range 4 - 20 cm). The final pathology results were: 9 benign lesions, 1 neuroendocrine tumor and 6 rectal adenocarcinomas, within these 4 cases were Tis, 1 was T1 sm1 and the other T1 sm2. 3 cases with preoperative adenoma biopsy turned out to have adenocarcinoma in the final pathology. The frequency of fragmented pieces was 6.3%. The mean postoperative stay was 4.4 days. The frequency of complications was 12.5%. No local recurrence was evident during follow-up. Conclusions. TAMIS is a safe, feasible and low-morbidity procedure for the resection of benign neoplasms and in selected cases of early-stage rectal cancer.